Faktor-Faktor Penentu Pengembangan Karier Karyawan Di Holiday Inn Resort Baruna Kuta Bali - Tanaya, Tjokorda Raka Febrian; Sari, Ni Putu Ratna; Pertiwi, Putu Ratih (Jurnal Kepariwisataan dan Hospitalitas, 2019)
Abstract TheBackgrounds of this research is employees career development at Holiday Inn Resort Baruna Bali. in 2016,  35 of career development has occurred around whole department I n this hotel. The objective to obtain out which factors could be determining employees carrer development and also to find out the dominan factor in determining employees carier development in Holiday Inn Resort Baruna Bali Kuta Bali. The data was obtained through observation, depth interview, quesstionnaire, literature studies and documentation. Proportional random sampling technique is used to selected 100 samples. Descriptive qualitative analysis technique was analyzed busing likert scale and quantitative analyzed using validity test, realibility test, and factor analysis by SPSS 22.0 program. career development variabel which has is 15 indicators. The result shows that the value of Measure of Sampling asequancy (MSA) is more than 0,5 , which means it can be proceeded to the factor analysis , and there is no factor should be ignored. There are 3 determinants factor of employee career development base on the result of determinant factor analysis where the value of loading factor is 63, 410 %. The first factor is mentor and sponsor with 45,499 % as the value. The second factor is status of position with 10,917 % as the value. And the third factor is resignation by own request with 6,993% as value. Base on those 3 factor the factor mentor and sponsor is where it has the eigenvalue of 6,825 and its variance value is 45,499 %. A dominant factors to determinats the employees career development in Holiday Inn Resort Baruna Kuta Bali. By this reseach hotel is suggested to increase the number of training that they have been conducted in order to improving the achievement of the employee and intensively giving a coach for the employee to help and support them in developing their career. Keywords: Career Development, Employees, Factors, Holiday Inn